Drug affinity-responsive target stability unveils filamins as biological targets for artemetin, an anti-cancer flavonoid - Ferraro, Giusy; Belvedere, Raffaella; Petrella, Antonello; Tosco, Alessandra; Stork, Björn; Salamone, Stefano; Minassi, Alberto; Pollastro, Federica; Morretta, Elva; Monti, Maria Chiara (Frontiers in Molecular Biosciences, 2022)
Artemetin is a valuable 5-hydroxy-3,6,7,3',4'-pentamethoxyflavone present in many different medicinal plants with a very good oral bioavailability and drug-likeness values, owing numerous bioactivities such as anti-inflammatory and anti-cancer ones. Here, a multi-disciplinary approach has been developed and applied for identifying Artemetin target(s) to fully address its mechanism of action, based on drug affinity response target stability and targeted limited proteolysis. Both approaches point to the identification of Filamins A and B as major Artemetin targets in HeLa cell lysates, giving also detailed insights on the ligand/proteins binding sites. Interestingly, also the 8-prenyl-Artemetin, which is an Artemetin more permeable semisynthetic analog, directly interacts with Filamin A and B. Both compounds alter filamins conformation in living HeLa cells with an effect on cytoskeleton disassembly and on the disorganization of the F-actin filaments. Both the natural compound and its derivative are able to block cell migration, expectantly acting on tumor metastasis occurrence and development.